Astronomy on the web a brief guide to the internet for Foundations of astronomy, by Seeds ... - Kurland, Daniel J. (Wadworth Publishing Co, 1999)
This guide is intended to teach students how to gather the latest astronomy updates on the Internet. Divided into two sections, the first provides the basics of getting access to and doing searches on the Internet, and the second lists useful websites in the field of astronomy.